Measurement madness : recognizing and avoiding the pitfalls of performance measurement - Gray, Dina, 1963-; Micheli, Pietro, 1978-; Pavlov, Andrey, 1981- (Wiley, 2015)
"The ultimate guide to performance management and how to avoid the often bizarre unintended consequences of KPIsThe results of well-intended performance measurement are sometimes bizarre and bewildering. World leaders in business performance, the authors of Measurement Madness have amassed a wealth of real-life business stories, producing this timely how-to guide for avoiding the unintended consequences that come from measuring people, processes and organizations.Measurement Madness is a lively and informative take on this topical subject. Peppered with anecdotal evidence, it uses case studies to reveal some of the more outrageous and unexpected outcomes of KPIs, but also to show what performance management success looks like. Management theories are used to underline types of behavior and, most importantly, how they can be anticipated.This book gives you guiding principles for avoiding common pitfalls, such as setting the wrong performance targets and measuring what is easy rather than what is useful. It provides reliable, practical advice demonstrating how to create meaningful performance measurement. Authors are from the world-leading Business Performance team at Cranfield University in the U.K. which has a world-renowned reputation for close partnerships with industry Case studies include U.S., U.K., and international examples of performance management from real business stories Ironically, Measurement Madness might just be the key to saving your sanity for the next round of performance management"--Resumé vydavatele
Keywords: měření výkonnosti; řízení pracovního výkonu; performance measurement; performance management; příručky; handbooks and manuals